2019
DOI: 10.1021/acs.analchem.8b04749
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor Discrete Frequency Infrared Spectroscopic Imaging

Abstract: Advancement of discrete frequency infrared (DFIR) spectroscopic microscopes in image quality and data throughput are critical to their use for analytical measurements. Here, we report the development and characterization of a point scanning instrument with minimal aberrations and capable of diffraction-limited performance across all fingerprint region wavelengths over arbitrarily large samples. The performance of this system is compared to commercial state of the art Fourier transform infrared (FT-IR) imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 45 publications
0
43
0
Order By: Relevance
“…3 ). This comparison is based on standard instruments, and more discussions on high-speed versions can be found in the literature 12 , 33 . Briefly, while the spatial resolution of SRS is expectedly finer, FTIR could be more advantageous to accommodate the full spectral coverage in a single scan ( Fig.…”
Section: Mir Microscopy As a Complementary Platform To Raman For Highmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). This comparison is based on standard instruments, and more discussions on high-speed versions can be found in the literature 12 , 33 . Briefly, while the spatial resolution of SRS is expectedly finer, FTIR could be more advantageous to accommodate the full spectral coverage in a single scan ( Fig.…”
Section: Mir Microscopy As a Complementary Platform To Raman For Highmentioning
confidence: 99%
“…We note the DFIR images have some speckle patterns under the widefield configuration. This can be potentially mitigated by spatial noise dephasing 21 , 37 or point scanning system 33 , 38 .…”
Section: Technical Demonstration Of Dfir Metabolic Imaging With Vibramentioning
confidence: 99%
“…Recent studies have demonstrated wide-field measures of photothermal absorption and scattering (52,53). Despite providing optical compatibility, however, these methods provide fields of view and pixel counts that are much smaller than direct absorption IR microscopy (54). More importantly, data exhibit relatively poor sensitivity compared to direct absorption IR microscopy as the beam deflection is a measure of the photothermal change in the refractive index.…”
Section: Significancementioning
confidence: 99%
“…Nanoscale IR spectroscopic mapping of polymer sample with a spatial resolution of 20 nm in the 1000–1500 and 1500–1900 cm −1 ranges was realized by scanning the sampled area in one direction . Quantum cascade lasers based DFIR spectroscopic microscope working at point scanning mode has been recently proposed for faster spectral imaging by optimizing the optical parameters and reducing the overlapped data . Supercontinuum source also promotes the design of a mid‐IR multispectral imaging system for the imaging of component distribution within a tissue, showing satisfying imaging quality and acquisition speed compared to a commercial instrument, which provides new ideas for microscale spectroscopic mapping of 2D materials.…”
Section: Spectroscopic Imagingmentioning
confidence: 99%